(untitled) (Journal Of Educational and Psychological Researches, 2014)
The research aimed at measuring the degree to which the accept their class environment in governmental & civil Kindergartens & it also aimed at knowing the differences between the dimensions of the measurement & the differences according to the kindergarten & class variables . The researcher made a measurement for the class environment & it included five dimensions & the answering choices were three ( to a big extent , to some extent and no ) and after making sure that the measurement is usable , the researcher applied it on the sample which consisted of ( 212 )male & female children through the estimated answers of the teacher & the result was that there was an acceptance of the children to their environment , & also their were differences in three dimensions of the measurement in favor of the research sample . Also , there was a difference in the other two dimensions in favor of society whereas there was no difference showing the children’s acceptance to their environment according to the kindergarten & class variables . In the light of the results of the research , the researcher asks for making an atmosphere of intimacy , love & amusement between the teacher & the child .